GCL Model by the determination of the characteristics in the beginning zone of the debris flows using a GIS - cardoso-lanza, Guillermo (Italian journal of engineering geology and environment, 2011)
In recent years an increase in the prevalence of debris flows has been observed in various regions of the world. These events, which have caused a significant amount of damage to cities, infrastructure and ecosystems; emphasize the importance of developing early warning systems to alert residents of the danger in advance. A model to determine the probability of occurrence of a debris flow through the development of a geographic information system that combines a digital elevation model and a distributed hydrological model is described.